2018
DOI: 10.1080/1354750x.2018.1466367
|View full text |Cite
|
Sign up to set email alerts
|

Global methylation profiles in buccal cells of long-term smokers and moist snuff consumers

Abstract: Chronic cigarette smoking causes hyper- and hypo-methylation of genes that could contribute to smoking-related diseases. These results help place combustible and non-combustible tobacco products along a risk continuum and provide additional insights into the effects of tobacco consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 59 publications
(77 reference statements)
2
13
0
Order By: Relevance
“…Our top hit identified in the SS model (cg05575921, p-value=4.54E-83) is within the AHRR gene, a well-known locus that acts in the aryl hydrocarbon receptor signaling cascade. This CpG was hypomethylated in current-smokers compared to non-smokers, as reported in other peripheral tissues including blood (9-12), lung (17,18), adipose tissue (19), and buccal cells (20). Further, 13 additional GWS DMS in AHRR were detected (minimum p-value = 5.73E-8), of which seven were previously described.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our top hit identified in the SS model (cg05575921, p-value=4.54E-83) is within the AHRR gene, a well-known locus that acts in the aryl hydrocarbon receptor signaling cascade. This CpG was hypomethylated in current-smokers compared to non-smokers, as reported in other peripheral tissues including blood (9-12), lung (17,18), adipose tissue (19), and buccal cells (20). Further, 13 additional GWS DMS in AHRR were detected (minimum p-value = 5.73E-8), of which seven were previously described.…”
Section: Discussionsupporting
confidence: 65%
“…DNA methylation (DNAm), one of the most studied epigenetic mechanisms, has been previously shown to be associated with smoking behavior. Epigenome-wide association studies (EWAS) approaches have identified epigenomic biomarkers associated with smoking in multiple tissues: blood (9)(10)(11)(12)(13)(14)(15), newborn blood (16), lung (17,18), adipose tissue (19), buccal cells (20), and saliva (21)). While a large number of CpG sites have been associated with tobacco smoking status (SS), few studies to date have examined epigenomic changes associated with ND.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of studies exist that show significantly different methylation patterns in smokers compared to non-smokers in different tissues [2, 822] and in the context of smoke-related diseases like cancer [23] or chronic obstructive pulmonary disease (COPD) [21]. The best-replicated gene-specific association of differential methylation with smoking is attributed to the aryl-hydrocarbon receptor repressor AHRR across various tissues and cell types [8, 10, 1214, 16, 17, 20, 22, 24, 25]. AHRR is a core regulator in the aryl hydrocarbon receptor (AhR) signalling cascade, modulating dioxin toxicity pathways involving Cytochrome P450, most likely in a cell-specific manner [26].…”
Section: Introductionmentioning
confidence: 99%
“…AHRR is a core regulator in the aryl hydrocarbon receptor (AhR) signalling cascade, modulating dioxin toxicity pathways involving Cytochrome P450, most likely in a cell-specific manner [26]. Most EWAS that assessed the role of CpG methylation in tobacco-related xenobiotic metabolism analysed leukocytes, but some also analysed airway epithelial cells [27] and buccal cells [12, 21, 22]. These cell types are located at the interface to the environment and form a mechanical and physiological barrier.…”
Section: Introductionmentioning
confidence: 99%
“…This study used a different swab type (Catch-All Sample Collection Swabs) with softer spongelike brushes possibly associated with less bleeding, and thus less contamination. On the other hand, a recent dataset of 120 samples related to tobacco usage from Jessen et al [32] was listed as originating from buccal cells, but showed an unusually low buccal content more typical of saliva datasets [28,33] as shown in Supplemental Figure S1. The authors reported that these buccal samples 'were collected in water by vigorously swishing' while the subjects rinsed their mouth, which may explain why the samples actually resemble the saliva.…”
Section: Lower-purity Buccal Samples Occur Commonlymentioning
confidence: 99%